2011
DOI: 10.1161/circresaha.110.235879
|View full text |Cite
|
Sign up to set email alerts
|

Redox Regulation of Soluble Epoxide Hydrolase by 15-Deoxy-Δ-Prostaglandin J 2 Controls Coronary Hypoxic Vasodilation

Abstract: Rationale 15-deoxy-Δ-prostaglandin J2 (15d-PGJ2) is an electrophilic oxidant that dilates the coronary vasculature. This lipid can adduct to redox active protein thiols to induce oxidative post-translational modifications that modulate protein and tissue function. Objective To investigate the role of oxidative protein modifications in 15d-PGJ2-mediated coronary vasodilation and define the distal signaling pathways leading to enhanced perfusion. Methods and Results Proteomic screening with biotinylated 15d-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
52
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 36 publications
4
52
0
Order By: Relevance
“…Consequently, sEH activity was measured in heart tissue, where NO 2 -OA treatment was observed to inhibit hydrolase activity in WT but not KI. It was also noted that the sEH activity in the KI was slightly less than WT, consistent with previous studies in transfected cells where it was observed that the cysteine-to-serine mutation similarly reduced EET hydrolysis (1). This suggests the explanation that the Cys521 thiol may provide protons necessary for EET hydrolysis and the addition of electrophiles to this thiol abrogates catalytic activity.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Consequently, sEH activity was measured in heart tissue, where NO 2 -OA treatment was observed to inhibit hydrolase activity in WT but not KI. It was also noted that the sEH activity in the KI was slightly less than WT, consistent with previous studies in transfected cells where it was observed that the cysteine-to-serine mutation similarly reduced EET hydrolysis (1). This suggests the explanation that the Cys521 thiol may provide protons necessary for EET hydrolysis and the addition of electrophiles to this thiol abrogates catalytic activity.…”
Section: Discussionsupporting
confidence: 88%
“…This "redox-inactive" sEH thiol mutant, rendered insensitive to adductive inhibition by lipid electrophiles in vitro, provided a novel model system for testing the impact of lipid nitroalkenes on sEH hydrolysis of vasoactive EET species and downstream physiological responses (1). The data reveal that nitro fatty acids, applied exogenously as a pharmacological agent or generated endogenously as part of the Mediterranean diet, inhibit sEH to elevate plasma EETs, which in turn lower BP.…”
Section: Significancementioning
confidence: 96%
See 2 more Smart Citations
“…This indicates that the ratios of EpETrEs/DiHETrEs are closely related with the function of sEHI. Other studies using lipids metabolic profiling also revealed that either the ratios of EpETrEs/ DiHETrEs or the increased EpETrEs is correlated with sEHI treatment and may be used as a potential biomarker to evaluate the engagement of sEHI [13][14][15][16][17].…”
mentioning
confidence: 99%